633Poorly controlled diabetes is a predictor of colorectal cancer survival. (2nd September 2021) - Li, Ming; Roder, David
Abstract: Background: Epidemiological studies have shown diabetes associated with increased risk of colorectal cancer. This study investigates the impact of a pre-cancer diabetes-related hospitalization record on colorectal cancer survival. Methods: A retrospective cohort of 13190 colorectal cancer patients recorded on the South Australian Cancer Registry in 2003-2013 were examined. Diabetes-related hospitalization histories were obtained using linked inpatient data. Colorectal cancer deaths were available for 2003-2013. The association of survival from colorectal cancer with diabetes-related hospitalization history was assessed using competing risk analysis, adjusting for sociodemographic factors and cancer stage at diagnosis. Results: 2765 patients with colorectal cancer (26.5%) had a history of hospital admission for diabetic complications, the most common being multiple complications (32%), followed by kidney and eye complications. The 5- and 10-year cancer survival probabilities were 63% and 56% in those with a diabetes complication history, significantly lower than 66% and 60% for patients without these complications (adjusted sub hazard ratio 1.11, 95% CI 1.02-1.20). Risk of colorectal cancer death was lower when theses diabetes-related hospitalizations were earlier than the year of cancer diagnosis - i.e., adjusted SHR 0.80, 95% CI 0.66-0.97 for 3-5 and 0.76, 95% CI 0.59-0.98 for 6+ years before the cancer diagnosis compared with same-year hospitalizations. Conclusions: Colorectal cancer patients with a history of diabetes-related hospitalization have poorer survival, particularly if these hospitalizations were in the same year as the cancer diagnosis. Key messages: Poorly controlled diabetes histories predict increased risk of colorectal cancer mortality.